2016
DOI: 10.1136/bcr-2016-215423
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of recurrent pleural and pericardial effusions with tocilizumab in a patient with systemic lupus erythematous

Abstract: A 22-year-old Caucasian man presented to hospital with pleuritic chest pain. He had had a history of a sun-sensitive rash a year prior. Workup revealed normal cardiac enzymes and chest X-ray. However, electrocardiogram revealed ST elevation and PR depression, and echocardiogram revealed a slight pericardial effusion without other findings. A diagnosis of pericarditis was made. Subsequently, he was found to be positive for antinuclear antibodies (ANAs), as well as antibodies to SSA, SSB and double-stranded DNA;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
0
16
0
2
Order By: Relevance
“…Another phase II study in SLE patients with the humanized monoclonal antibody tocilizumab against the chain of the IL-6 receptor, showed a reduction of auto-antibodies production and plasma-cells and significant clinical improvement especially in case of arthritis and fatigue (Illei et al, 2010). Finally a case report demonstrated the efficacy of tocilizumab in lupus serositis (Kamata and Minota, 2012; Ocampo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another phase II study in SLE patients with the humanized monoclonal antibody tocilizumab against the chain of the IL-6 receptor, showed a reduction of auto-antibodies production and plasma-cells and significant clinical improvement especially in case of arthritis and fatigue (Illei et al, 2010). Finally a case report demonstrated the efficacy of tocilizumab in lupus serositis (Kamata and Minota, 2012; Ocampo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The tocilizumab is another monoantibody directed against IL-6 receptor and blocks the downstream signal pathway by which it modulates the function of IL-6R expressing T and B cells. This agent was successfully administrated to patients with lupus-associated serositis [ 53 ], massive pericarditis, and glomerulonephritis [ 52 , 54 ]. In autoimmunity, combination therapy with anti-IL-1 β and anti-IL-6 antibody has not been tested so far.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of circulating T and B cell subsets in patients with SLE showed that TCZ decreased the frequency of plasmablasts/plasma cells and memory B cells but increased the concentrations of antigen-inexperienced B cells and naïve T cells, suggesting the restoration of B and T cell homeostasis [ 157 ]. A case report also indicated that TCZ was effective for recurrent pleural and pericardial effusion in patients with SLE [ 158 ]. Further clinical studies are required to confirm the efficacy of TCZ on SLE.…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%